SEMANTIC AND CULTURAL CHARACTERISTICS OF PHRASEOLOGICAL UNITS WITH ONOMASTIC COMPONENTS IN TURKIC LANGUAGES: A COMPARATIVE ANALYSIS OF AZERBAIJANI, TURKISH, KAZAKH, KYRGYZ AND UZBEK - Aysu Mirzayeva (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study examines the relationship between onomastics and phraseology in Turkic languages. It analyzes how proper names (anthroponyms, toponyms, ethnonyms) undergo semantic transformation within phraseological units. Focusing on Azerbaijani, Turkish, Kazakh, Kyrgyz, and Uzbek, it shows how names shift from simple identifiers to cultural archetypes through deonomastization. Using comparative-typological and ethnolinguistic approaches, the research highlights the influence of geographical settings and historical layers on the worldview of Turkic peoples. The findings reveal that despite regional differences in onomastic elements, shared cognitive mechanisms and mythological foundations function as a common cultural “genetic code” across the Turkic world.